(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: Our study is conducted to identify serotypes, antibiotic resistance, heavy metal resistance, and virulent genes in Escherichia coli isolated from goats raised in small-scale farms in some provinces of the Mekong Delta, Vietnam. Material and Methods: A total of 203 E. coli isolates from goat feces were examined by PCR for serotypes (O8, O9, O25, O26, O45, O103, O146, O157, and O159), eight antibiotic-resistance genes, four heavy-metal-resistance genes, and four pathogenic genes. Results: By PCR, 20.20% of E. coli isolates belonging to serotypes O8 (6.40%), O45 (13.30%), and O159 (0.49%) were identified. Antibiotic-resistance genes were recorded at high rates in E. coli isolates, especially genes blaampC (98.52%), tetA (50.74%), sulII (34.48%), qnrA (20.69%), and aadA1 (20.69%). Moreover, 55.67% of these E. coli isolates harbored multiple antibiotic-resistance genes. Among heavy-metal-resistance genes, the gene czcD encoding for resistance to cobalt, zinc, and cadmium was the most prevalent (59.11%). In addition, the most frequent virulent gene was stx1 (15.27%), followed by gene stx2 (6.90%), eae, and hlyA (1.48%). Conclusion: These results revealed that goats were a natural reservoir of pathogenic E. coli serotypes, which could cause severe diseases in animals and humans. Moreover, these E. coli isolates showed a high ability to resist diverse antibiotics. Thus, managing the prevalence of pathogenic E. coli is essential for protecting public health in the Mekong Delta. J. Adv. Vet. Anim. Res., 12(2): 420–426, June 2025 http://doi.org/10.5455/javar.2025.l908